ANALISIS PENGARUH ZIS TERHADAP PEREKONOMIAN INDONESIA - Hairunnisa; Maysaroh; Salwa (Program Studi Ekonomi Syariah, 2021)
As a country with the largest Muslim majority in the world, Indonesia can take advantage of this potential to improve the economy by empowering people through ZIS (Zakat, Infaq and Sadaqah). As revealed by BAZNAS, Indonesia's zakat potential can reach Rp. 217 trillion and the potential for zakat of that size is able to reduce the number of poor people in 21 provinces. Not to mention if you add the potential for alms and infaq, the amount can be almost doubled. Based on that, the objectives of this study are: 1) To find out how ZIS influences the Indonesian economy, 2) To identify ZIS revenue has a significant or no effect on the Indonesian economy. This study uses quantitative and qualitative data analysis. Secondary data was obtained from the official websites of related institutions (BAZNAS and BPS) which were tested with the Eviews application through the Classical Assumption Test and Multiple Regression Test. The results of this study are as follows: 1) Based on the results of qualitative analysis, it is known that the number of ZIS receipts (zakat, infaq and shadaqah) from 2011 to 2018 has increased significantly both in semester I and semester II. This data shows that the potential for zakat in Indonesia is increasing. Meanwhile, the number of Gross Domestic Product (GDP) increased from 2011 to 2018 per semester. The highest increase occurred in 2018, namely in the first semester of 7,236,927.10 and in the second semester of 7,640,430,40. 2) ZIS has a significant effect on the Indonesian economy. Based on the results of the analysis and discussion in this study, it can be concluded that based on the results of the classical assumption test, no violations occurred. Meanwhile, in the multiple regression test, the probability value is 0.0582, which is greater than the significance level or (0.05/0.01/0.1). Thus H0 is accepted. This shows that the ZIS variable has a significant effect on the GDP variable. The conclusion of this study is that ZIS has an effect on economic growth.